A Comparison of Students' Approaches to Inquiry, Conceptual Learning, and Attitudes in Simulation‐Based and Microcomputer‐Based Laboratories. Issue 5 (September 2014) - CHEN, SUFEN; CHANG, WEN‐HUA; LAI, CHIH‐HUNG; TSAI, CHENG‐YUE
ABSTRACT The purpose of this project was to investigate the effects of virtual versus physical manipulation using a simulation‐based laboratory activity (SBL) and a microcomputer‐based laboratory activity (MBL). Both the SBL and the MBL used computers to collect, graph, and analyze data. A major difference was that the MBL allowed the students to manipulate physical materials, whereas in the SBL activity they manipulated virtual materials. In this quasi‐experimental design, two 11th‐grade classes (N = 68) at an urban public high school in Taipei were assigned to the SBL and MBL settings. The participants conducted the Boyle's law experiment without having done any relevant prior experiment. Their science concepts, performance of inquiry tasks, and attitudes toward the SBL/MBL were examined by pre‐ and postconceptual tests, an inquiry‐based lab manual, and postlaboratory interviews. The results showed that both groups performed equally well and had remarkable gains in their pre‐ to posttest learning achievement. Nevertheless, physical manipulation may have contributed to inquiry practices such as creating practical ideas for conducting and improving the experiment and interpreting the data and may have increased the enjoyment of the laboratory. This study concludes that virtual manipulation is as effective as physical manipulation in learning physics concepts, but that the former gives learners some naïve expectations and induces certain learning strategies that seem to lead to mindless planning and conducting of experiments and hinders them from generating ideas to improve experiments.